Insect Pest Diversity on Maize Farming at UPT Tanjung Selamat, Deli Serdang Regency: A Case Study - Ria Lanti Sinaga; Arlen Hanel Jhon; Erni Jumilawaty (International Journal of Ecophysiology, 2024)
UPT Tanjung Selamat located in North Sumatra is one of significant corn farming areas in North Sumatra which currently faces disturbance from insects. This study investigates insect pest diversity in corn fields at two growth stages, 25 and 60 days after planting (DAP), within the UPT Tanjung Selamat area of Deli Serdang Regency. Yellow sticky traps were installed in designated sites as approaches to collect and identify insect pest community in the area. Our results showed that at 25 DAP, three pest species were identified, while at 60 DAP, seven species were recorded, showcasing higher diversity at the latter stage. The insect pest with the highest population density at both growth stages of maize is Cicadulina bipunctata, with 48.12 ind/m² at 60 DAP and 36.67 ind/m² at 25 DAP. The total insect pest density peaked at 60 DAP (61.44 individuals/m²) and reached its lowest at 30 DAP (49.38 individuals/m²). Similarly, the diversity index was highest at 60 DAP (1.283), contrasting with the lowest value at 25 DAP (0.652). The evenness index mirrored these trends, peaking at 60 DAP (0.659) and reaching its lowest at 25 DAP (0.593). The Sorensen similarity index indicated a 60% similarity between the two periods, reflecting relatively similar insect pest compositions. These findings highlight the dynamic nature of insect pest populations in maize fields at different growth stages, emphasizing the need for age-specific management strategies. This study contributes valuable insights for optimizing pest control measures and promoting sustainable corn production practices.